How does the implementation of critical reading strategies raise the levels of social awareness related to the current post-conflict period in students of 8th grade? (2018)
ABSTRACT: Responding to one of the main challenges currently faced by the Colombian society after the approval of the peace process agreement, this action research was developed with the objective of describing the increase of social awareness in a group of high school students through the implementation of critical reading strategies related to the post-conflict period in our country. The participants involved in this project were a group of female students whose ages ranged from 13 to 14 years old who attended Institucion Educativa San Jose de Itagui. Data was collected through the implementation of techniques such as surveys, interviews, journals, and students´ artifacts. The analysis was conducted under a triangulation process framed on the principles of the socio-critical approach. Findings evidenced that students´ perception towards the post conflict changed. They found themselves as part of the current history of the country. Students started to recognize the importance of examining their prejudices and stereotypes before judging a person. Debates and discussions promoted collaboration, recognition and acceptance. Critical reading strategies on social issues related to the post-conflict had a positive impact and increase the level of students’ social awareness.